Kontribusi Pemikiran Islam Dalam Peradaban Melayu - Muhammad Torik; Muhammad Abdillah; Fenti Febriani (Medina-te : Jurnal Studi Islam, 2022)
This study aims to seethe contributionbof Islamic thought in civilization of malay and then becomes a separate study within the scope of malay Islamic studies, as historical records have confirmed that developments that happened in Islamic world also have a contribution in a progress malay civilization, form both of these gave an identity to the public of malay. There are at least two questions that submitted in this study (1) how is the history of the development Islamic civilization; (2) how is the Islamic contribution in civilization of malay. The method used is about how to find library datas and interpreting the data found in reference sources and various supporting sources about the contribution of Islamic thought in the world of malay, this is complementwd of Islam with an indirect approach. the contribution of Islamic thought and civilization can be seen from history and culture, both of which are the identity of a nation, from these two things will be seen the history of identity and historical identity. Hinduism and Buddhism, followed by the Hindu and Buddhist periods, the arrival of Islam, after that the colonial period of colonialism over Malays, but the influence of Islamic thought on Malay civilization until now is very strong, even this influence dominates the influence of other religious thoughts.